Expertise-driven temporal gaze dynamics during anticipation in volleyball - Kanatschnig, T.; Korda, Ž.; Schrapf, N.; Leitner, L.; Anzengruber, C.; Lappi, O.; Körner, C.; Tilp, M.; Kober, S. E. (PLOS ONE, 2025)
Perceptual-cognitive comparisons of experts and novices have consistently shown that experts use specific visual strategies to process visual scenes in their domain of expertise, reflected in eye movement metrics such as fixation rates and durations. We present an investigation of the gaze behavior from professional volleyball players (experts; n = 14) during a volleyball anticipation task and compare them to intermediate level volleyball players (amateurs; n = 25) and individuals with only basic volleyball experience (novices; n = 19). The task consisted of the observation of videos, which were recorded during official national level volleyball matches, each showing unique setting situations. Our results replicate previous findings showing lower fixation rates as well as longer fixation durations in relation to higher expertise. Yet, this trend was only present in the later phase of video observation, i.e., during the course of the rally. In the early phase, i.e., during players` preparation before the service, experts did not differ from amateurs on all fixation metrics, while novices performed comparatively higher rates of fixations. Our findings emphasize the importance of investigating temporal dynamics, as well as using a comprehensive operationalization of perceptual-cognitive processes related to expertise.